Buddhist Philosophy and Its Relevance in the Present Times: बुद्ध दर्शन और वर्तमान में उसकी प्रासंगिकता - Poonam; Kumar, Pintu (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Gautama Buddha’s philosophy, rooted in the Four Noble Truths, the Eightfold Path, impermanence, non-self, karma, compassion, and non-violence, offers a rational and experiential framework for addressing human suffering. This paper explores the relevance of Buddhist philosophy in tackling modern challenges such as mental health crises, environmental degradation, and social inequalities. The Four Noble Truths provide insights into the nature of suffering and its cessation, while the Eightfold Path offers practical ethical guidance. Concepts like impermanence and interconnectedness resonate with environmental sustainability, and mindfulness practices address contemporary mental health issues. Compassion and non-violence promote social harmony, making Buddhist philosophy a timeless guide for personal and societal well-being in today’s complex world.Abstract in Hindi Language: गौतम बुद्ध का दर्शन, जो चार आर्य सत्य, अष्टांगिक मार्ग, अनित्यता, अनात्म, कर्म, करुणा और अहिंसा पर आधारित है, मानव दुखों को समझने और समाधान के लिए तर्कसंगत और अनुभव-आधारित ढांचा प्रदान करता है। यह शोध पत्र आधुनिक चुनौतियों जैसे मानसिक स्वास्थ्य संकट, पर्यावरणीय क्षरण और सामाजिक असमानता में बौद्ध दर्शन की प्रासंगिकता का विश्लेषण करता है। चार आर्य सत्य दुख की प्रकृति और उसके निरोध को समझाते हैं, जबकि अष्टांगिक मार्ग नैतिक मार्गदर्शन प्रदान करता है। अनित्यता और प्रतीत्यसमुत्पाद पर्यावरणीय स्थिरता से जुड़ते हैं, और माइंडफुलनेस मानसिक स्वास्थ्य के लिए प्रभावी है। करुणा और अहिंसा सामाजिक सौहार्द को बढ़ावा देते हैं, जिससे बौद्ध दर्शन आधुनिक विश्व में व्यक्तिगत और सामाजिक कल्याण के लिए प्रासंगिक है।Keywords: बौद्ध दर्शन, चार आर्य सत्य, अष्टांगिक मार्ग, माइंडफुलनेस, अनित्यता
Keywords: Buddhism; Four Noble Truths; Eightfold Path; mindfulness; impermanence